Relevant Restaurant Interests to Partnering with Non-Profit Organizations - Schick, Tracey; Stephen, Marla; Oatway, William Keenan; Phillips, Adam (MacEwan University Student eJournal, 2015)
Mealshare is a newly formed non-profit organization that partners with restaurants to feed persons in need. We conducted exploratory and quantitative research on Edmonton and area restaurants to identify those restaurant interests leading to partnerships with non-profit organizations. By performing in-depth interviews with restaurant owners and managers within Edmonton, we discovered main themes such as marketing benefits of social responsibility, preferences for charities to donate to, concerns about charity work, and influences on choosing social responsibility efforts. A questionnaire was developed and distributed to restaurant owners and managers, from which we derived tentative conclusions and recommendations to enhance the Mealshare brand and identify future opportunities. Based on the findings, we find that Mealshare should focus on configuring their marketing activities to emphasize community involvement, time constraint management, and marketing benefits, as well as tailor themselves for independently owned restaurants.